A teleconsultation network improves the efficacy of anti-VEGF therapy in retinal diseases. (December 2013) - Azzolini, Claudio; Torreggiani, Aldo; Eandi, Chiara; Donati, Simone; Oum, Muna Al; Vinciguerra, Riccardo; Bartalena, Luigi; Tartaglia, Valerio
We investigated the care of patients with age-related macular degeneration (AMD) managed via a physician-to-physician teleconsultation network for ophthalmology. Eleven groups of ophthalmologists took part in the study. The groups were located in 10 cities across Italy. Each group was based on a Retina Centre located at a university or hospital, with one or two expert ophthalmologists (20 expert ophthalmologists in total). In each region containing a Retina Centre, 6-10 general ophthalmologists (94 ophthalmologists in total) referred patients via the network for a period of three months between June 2011 and December 2012. An automatic grading system quantified the risk of disease progression, and a remote booking system allowed the referring ophthalmologist to make appointments directly with the appropriate Retina Centre. There were 360 network patients and 318 control patients (consecutive patients undergoing usual care during the previous three months). The time delay before therapy was significantly shorter in the network patients (mean 5.5 days) compared with the usual care patients (mean 28.7 days; P < 0.0001). There was a significant improvement in visual acuity in the network patients after treatment (first visit = 0.29 logMAR; after treatment = 0.22 logMAR; P < 0.05). In contrast, there was no improvement in the usual care patients (first visit = 0.29 logMAR; after treatment = 0.27 logMAR; P > 0.05). The telemedicine network allows regional ophthalmologists to quantify the risk of disease progression, and to send patients to a Retina Centre quickly and easily, when required.